Calpain-1 and Calpain-2 in the Brain: Dr. Jekill and Mr Hyde? - Baudry, Michel (Curr Neuropharmacol, 2019)
While the calpain system has now been discovered for over 50 years, there is still a paucity of information regard-ing the organization and functions of the signaling pathways regulated by these proteases, although calpains play critical roles in many cell functions. Moreover, calpain overactivation has been shown to be involved in numerous diseases. Among the 15 calpain isoforms identified, calpain-1 (aka µ-calpain) and calpain-2 (aka m-calpain) are ubiquitously distributed in most tissues and organs, including the brain. We have recently proposed that calpain-1 and calpain-2 play opposite functions in the brain, with calpain-1 activation being required for triggering synaptic plasticity and neuroprotection (Dr. Jekill), and calpain-2 limiting the extent of plasticity and being neurodegenerative (Mr. Hyde). Calpain-mediated cleavage has been ob-served in cytoskeleton proteins, membrane-associated proteins, receptors/channels, scaffolding/anchoring proteins, and pro-tein kinases and phosphatases. This review will focus on the signaling pathways related to local protein synthesis, cytoskele-ton regulation and neuronal survival/death regulated by calpain-1 and calpain-2, in an attempt to explain the origin of the op-posite functions of these 2 calpain isoforms. This will be followed by a discussion of the potential therapeutic applications of selective regulators of these 2 calpain isoforms.